A Discource on the Market Reaction to the Fatwa Nr. 83 of 2023 of the Majelis Ulama Indonesia (MUI): Case Study on Companies Listed on the Indonesian Sharia Stock Index (ISSI) - Ramadhani, Safira Kamalia; Nurhidayat, Nurhidayat (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2024)
The study aims to measure the market reaction of manufacturing and modern retail companies listed on the Indonesian Sharia Stock Index (ISSI) in response to the Majelis Ulama Indonesia (MUI) or the Indonesian Ulema Council Fatwa No. 83 of 2023 regarding the recommendation to boycott Israeli-affiliated products. The reaction was measured based on 2 indicators, abnormal return and trading volume activity. The methodology used in this study is quantitative with an event study type of research, where observations are made on the average abnormal return and trading volume activity of companies for 30 days before and after the release of the fatwa. The determination of the sample used a purposive sampling technique from 17 companies as samples. The analysis technique used is comparative analysis which includes descriptive analysis, normality test, and hypothesis testing using paired sample t-test and Wilcoxon signed rank test. The results of this study indicate there is no significant abnormal return or average trading volume activity before and after the event for companies in the manufacturing sector and modern retail listed in the ISSI. Keywords: Abnormal Return; Trading Volume Activity; Fatwa; Manufacturing Sector; Modern Retail Sector